2017
DOI: 10.1002/2017gl074953
|View full text |Cite
|
Sign up to set email alerts
|

Seismic High Attenuation Region Observed Beneath Southern New England From Teleseismic Body Wave Spectra: Evidence for High Asthenospheric Temperature Without Melt

Abstract: Seismic attenuation exhibits strong geographic variability in northeastern North America, with the highest values associated with the previously recognized Northern Appalachian Anomaly (NAA) in southern New England. The shear wave quality factor at 100 km depth is 14 < Q S < 25, the ratio of P wave and S wave quality factors is Q P /Q S = 1.2 ± 0.03 (95%), and the frequency dependence parameter is α = 0.39 ± 0.025 (95%). The high values of Q P /Q S and α are compatible with laboratory measurements of unmelted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 70 publications
(132 reference statements)
1
29
1
Order By: Relevance
“…However, simply based on the seismic tomographic images, we cannot rule out other possible causes for the observed low-velocity anomalies. Dong and Menke (2017) discovered strong seismic attenuations associated with the SNE-ENY anomaly at the depth of~100 km, which could be explained by a modern high-temperature anomaly alone. More recent studies have also suggested that the SNE-ENY low-velocity anomaly may be a recently formed feature (Dong & Menke, 2017;Levin et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, simply based on the seismic tomographic images, we cannot rule out other possible causes for the observed low-velocity anomalies. Dong and Menke (2017) discovered strong seismic attenuations associated with the SNE-ENY anomaly at the depth of~100 km, which could be explained by a modern high-temperature anomaly alone. More recent studies have also suggested that the SNE-ENY low-velocity anomaly may be a recently formed feature (Dong & Menke, 2017;Levin et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…A temperature increase of 120°C in the upper mantle contributes to~2.5% to the reduction of shear velocities (Goes et al, 2000). A recent study by Dong and Menke (2017) suggested the SNE-ENY anomaly as a modern high-temperature anomaly. However, the surface heat flow in the Adirondack Mountains area (35-40 mW/m 2 ) is notably lower than that in the New England region (55-75 mW/m 2 ; Blackwell et al, 2011;Nathenson & Guffanti, 1988).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This higher temperature of 1520–1670 °C at the top of the asthenosphere is at or above the peridotite solidus (melting) temperature of ~1500 °C (Mazza et al, , their Figure 4A). However, Dong and Menke () argue that the frequency dependence of the quality factor of Q S ∝ f 0.39 is not consistent with the widespread presence of melt (although small amounts might be present locally).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies that include data from the Transportable Array have established that the NAA has the following properties. The central, most intense part of the anomaly ( V S < − 3 % ) is about 400 km in diameter (Schmandt & Lin, ); has relatively sharp western and northern edges that roughly parallel the western margin of Laurentia (Menke et al, ); has its peak expression in the shallow asthenosphere at about 200‐km depth (Skryzalin et al, ); has a ratio of compressional‐to‐shear velocity fluctuations of Δ V P /Δ V S ~1.0 (Menke et al, ) and shear wave quality factor of Q S ~20 (Dong & Menke, )) consistent with a thermal origin; and is associated with reduced shear wave splitting (Levin et al, ) indicative of vertical flow. The thermal anomaly is inferred to be very large, 770 ± 180 ° C higher than the adjacent cratonic lithosphere, which is 850–900 °C at 100‐km depth (Menke et al, ).…”
Section: Introductionmentioning
confidence: 99%